基于现行标准实施后市售一级大豆油品质分析 "Quality analysis of commercially available grade 1 soybean oils after the national standard revision" - 陈焱1，王翔宇1，尤梦圆1，刘芯羽1，李晓龙1，孙承国2，王风艳2 " CHEN Yan1, WANG Xiangyu1, YOU Mengyuan1, LIU Xinyu1, LI Xiaolong1, SUN Chengguo2,WANG Fengyan1" (Zhongguo youzhi)
为了解大豆油目前的加工情况，基于国家标准中对大豆油相关指标的控制要求，对12个品牌市售一级大豆油的理化指标、营养指标及危害物指标进行了分析。结果表明：12个市售一级大豆油的酸值（KOH）在0.054~0.183 mg/g之间，过氧化值在0.59~2.01 mmol/kg，色泽均较浅；12个市售一级大豆油中维生素E和甾醇含量均值分别为113.06 mg/100 g和3 028 mg/kg，多酚和角鲨烯含量均值分别为4.82 mg/kg和53.71 mg/kg；12个市售一级大豆油中反式脂肪酸含量在0.25%~0.92%之间， 仅有1个样品的反式脂肪酸含量达到零反式脂肪酸的要求（低于0.3%）， 3-氯丙醇酯含量在0.23~0.57 mg/kg之间，平均值为0.38 mg/kg，缩水甘油酯含量为未检出~3.42 mg/kg，平均值为1.0 mg/kg，有3个样品的缩水甘油酯含量高于欧盟的限量要求，多环芳烃含量为未检出~8.8 μg/kg之间，平均值为4.77 μg/kg，苯并(a)芘含量为未检出~1.4 μg/kg，平均值为0.61 μg/kg。综上，大豆油生产企业应依据适度加工的原则，在保证产品品质符合要求的同时，尽可能多地保留营养物质，并减少危害物的生成。 In order to understand the current processing situation of soybean oil, based on the control requirements of soybean oil related indexes in the national standards, the physicochemical indexes, nutritional indexes and hazardous substance indexes of 12 brands of commercially available grade 1 soybean oils were analyzed. The results showed that the acid value of the 12 commercially available grade 1 soybean oils ranged from 0.054 mgKOH/g to 0.183 mgKOH/g, the peroxide value ranged from 0.59 mmol/kg to 2.01 mmol/kg, and the colour were light. The mean values of the vitamin E, sterol, polyphenol and squalene contents were 113.06 mg/100 g, 3 028 mg/kg, 4.82 mg/kg and 53.71 mg/kg, respectively. The trans fatty acid content ranged from 0.25% to 0.92%. Among the 12 commercially available soybean oils, only 1 sample met the requirement of zero trans fatty acid (less than 0.3%). the content of 3-chloropropanol esters ranged from 0.23 mg/kg to 0.57 mg/kg, with an average value of 0.38 mg/kg,and the content of glycidyl esters ranged from non-detected to 3.42 mg/kg, with an average value of 1.0 mg/kg, of which the glycidyl esters content of 3 samples was higher than the EU limit. The content of polycyclic aromatic hydrocarbons ranged from non-detected to 8.8 μg/kg, with an average value of 4.77 μg/kg, and the content of benzo(a)pyrene ranged from non-detected to 1.4 μg/kg, with an average value of 0.61 μg/kg. In summary, soybean oil manufacturers should adhere to the principle of moderate processing, retaining the nutrients and reducing the generation of hazardous substances as far as possible while ensuring that the product quality meets the required standards.